Juridical Analysis of the 2024 Election Dispute and Its Implications for Democratic Integrity - Rasji, Rasji; Fadloli, Muhammad; Najla, Tengku Amira (CV. Rayyan Dwi Bharata, 2024)
Popular sovereignty is usually explained in the constitution through the form of a popular government system or a democratic state. This means that the state in running its government follows the law (rule of law) and is not based solely on power without rules (authoritarian state). General elections are one of the main pillars of a healthy democratic system. This research is normative juridical legal research carried out by identifying and conceptualizing law as a real and functional social institution in real life. The approach used emphasizes empirical research by going directly into the field. The nature of this research is descriptive using a statutory approach and an analytical approach. As the holder of judicial power, the special judiciary must ensure the application of law and justice. The Special Election Court needs to have express authority to hear cases in its jurisdiction. It is necessary to consider whether a single body is in the capital city or per province. In the context of dispute resolution, there are also regulations regarding dispute resolution authority. This authority is not only limited to the jurisdiction of the judiciary, but is also given to parties who are mandated by statutory regulations to resolve disputes, both formally and informally. The same thing applies in resolving election disputes, where not only courts or judicial authorities have the authority to adjudicate, but also other institutions in accordance with applicable legal provisions.